In vitro evaluation of erythromycin incorporated with β-cyclodextrin and povidone polymers for capsule drug delivery - Didacus Nnamani; Emokpae George; Alonge Abimbola; Nathaniel Onyenwe (Shiraz University of Medical Sciences, 2024)
Entrapment of drugs within polymers have been used to modify dosage drug release. The aim of this work is to compare the entrapment potentials of water soluble povidone and or β-cyclodextrin polymers in encapsulated erythromycin. Drug-polymer interaction was determined using FTIR, SEM and DSC. Using 23 factorial design, 8 variant polymer combinations were devised. Wetted erythromycin and polymer mix was kneaded and granulated. The granules were dried and analysed for drug-loading and micromeritic properties before being filled into a hard gelatin capsule. The capsules were analysed for physicochemical and antimicrobial properties. The FTIR spectrum of the drug-polymer depicts the leading peaks of erythromycin. SEM images and DSC thermogram of the drug-polymers showed irregular fluffy and porous structures, and reduction in endothermic temperatures respectively. The granules showed Carr's index, Hausner ratios and angle of repose < 24.07, 1.31 and 30.51° respectively, and over 97.81 % drug entrapment. All capsules met USP specification for weight uniformity. Erythromycin-povidone capsules disintegrated within 15 min, had 53 % dissolution in 15 min, and 53 - 100 % dissolution within 180 min. At 25 mg/ ml, erythromycin-povidone capsule gave zones of inhibition of 37.67 - 39.83 mm. FTIR analysis of the erythromycin-polymer mix indicated compatibility of erythromycin with the polymers, the SEM indicated formation of amorphous complex, while the DSC inferred non-complex interaction and improvement in solubility. In comparison with formulations with erythromycin-β cyclodextrin complex, erythromycin-povidone complex showed better promise in enhancing erythromycin capsule formulation and antimicrobial properties.